Is there a value for probiotic supplements in gestational diabetes mellitus? A randomized clinical trial. Issue 1 (December 2015) - Dolatkhah, Neda; Hajifaraji, Majid; Abbasalizadeh, Fatemeh; Aghamohammadzadeh, Naser; Mehrabi, Yadollah; Mesgari Abbasi, Mehran
Abstract Background Although several studies have found probiotics encouraging in prevention of gestational diabetes mellitus (GDM), the evidence for the use of probiotics in diagnosed GDM is largely limited. The aim of this study was to assess the effect of a probiotic supplement capsule containing four bacterial strains on glucose metabolism indices and weight changes in women with newly diagnosed GDM. Methods Sixty-four pregnant women with GDM were enrolled into a double-blind placebo-controlled randomized clinical trial. They were randomly assigned to receive either a probiotic or placebo capsule along with dietary advice for eight consecutive weeks. The trend of weight gain along with glucose metabolism indices was assayed. Results During the first 6 weeks of the study, the weight gain trend was similar between the groups. However, in the last 2 weeks of the study, the weight gain in the probiotic group was significantly lower than in the placebo group (p < 0.05). Fasting blood sugar (FBS) decreased in both intervention (from 103.7 to 88.4 mg/dl) and control (from 100.9 to 93.6 mg/dl) groups significantly, and the decrease in the probiotic group was significantly higher than in the placebo group (p < 0.05). Insulin resistance index in the probiotic group had 6.74 % reduction over the study period (p < 0.05). In the placebo group, however, there was an increase in insulin resistance index (6.45 %), but the observed change in insulin resistance was not statistically significant. Insulin sensitivity index was increased in both groups. The post-intervention insulin sensitivity index in the probiotic group was not significantly different from placebo when adjusted for the baseline levels. Conclusions The probiotic supplement appeared to affect glucose metabolism and weight gain among pregnant women with GDM. This needs to be confirmed in other settings before a therapeutic value could be approved.